2005
DOI: 10.1093/humrep/dei254
|View full text |Cite
|
Sign up to set email alerts
|

Y chromosome microdeletions: are they implicated in teratozoospermia?

Abstract: Our observations suggest that some of the teratozoospermia might be related to gonadal mosaic Y chromosome microdeletions. Gonadal mosaicism can be a source of de novo transmissions of Y chromosome microdeletions. The application of MDA can yield enough DNA from a single sperm for genetic analyses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
6
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 43 publications
1
6
1
Order By: Relevance
“…These deletions can be considered as nonfunctional variations because they occurred in all groups. Similar results were found by Hellani et al (2005), who reported a deletion of STS 5, 6, 10, 9, 13, and 14 in the normozoospermia group, with a sperm count of more than 20 × 10 6 spz/mL. In our study the deletions of all other STSs can be considered functional and important in the development of spermatogenesis, because they were significantly associated with a severe spermatogenic phenotype.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…These deletions can be considered as nonfunctional variations because they occurred in all groups. Similar results were found by Hellani et al (2005), who reported a deletion of STS 5, 6, 10, 9, 13, and 14 in the normozoospermia group, with a sperm count of more than 20 × 10 6 spz/mL. In our study the deletions of all other STSs can be considered functional and important in the development of spermatogenesis, because they were significantly associated with a severe spermatogenic phenotype.…”
Section: Discussionsupporting
confidence: 92%
“…In the last few years, the Y chromosome—specific sequence tagged site (STS) markers were used in a great number of clinical studies to identify microdeletions in DNA from peripheral blood lymphocytes (Kleiman et al, 2001) and from sperm (Hellani et al, 2005) of infertile males. Many publications have determined the prevalence of such deletions in male infertility.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…7607, Umm Al-Qura University, Makkah, KSA; Mobile: +966-553692180; Fax: +966-2-5270000 (ext 4659); E-mail: nasgenet@hotmail.com; naelhawary@uqu.edu.sa DNA from blood [5] and sperm [6] of infertile men. Most studies have focused on men with low sperm counts, so most of the deletions that have been found are associated with azoospermia and severe oligospermia.…”
Section: Introductionmentioning
confidence: 99%
“…To validate the aCGH results, we performed FISH under standard procedures using a whole chromosome 19 painting probe (WCP19; Oncor TM , Paris, France) on metaphases of the patient and his father. To confirm the integrity of the Y chromosome, amplification of the SRY gene and 22 sequence-tagged sites belonging to AZFa, AZFb, and AZFc regions and the Yq12 heterochromatin (sY160) was performed by multiplex PCR (conditions available upon request) according to primer sequences reported by Hellani et al [2005] and Krausz et al [2014].…”
Section: Cytogenetic and Molecular Analysismentioning
confidence: 99%